Book Review: Helping Library Users with Legal Questions: Practical Advice for Research, Programming, and Outreach - Gambill West, Agnes (Journal of Copyright in Education & Librarianship, 2021)
Deborah A. Hamilton’s new book sheds light on the access to justice crisis in the American legal system and illustrates valuable strategies for how libraries can help. Hamilton’s passion for assisting the public with research and discovery of legal information makes her well-suited to share practical advice for research, programming, and outreach related to legal information literacy. Hamilton’s message to readers is clear: libraries can play a significant role in making the justice system more accessible and equitable by providing access to laws and legal information.